Adults' and 8‐Year‐Olds' Learning in a Foreign Word Repetition Task: Similar and Different. Issue 2 (26th April 2014) - Service, Elisabet; Yli‐Kaitala, Hely; Maury, Sini; Kim, Jeong‐Young
<x xml:space="preserve">Abstract</x> Although the significance of age in second language acquisition is one of the most hotly debated issues in the field, very few studies have directly addressed age differences in the language learning process. The present study investigated learning in a foreign‐word repetition task. Young Finnish adults and 8‐year‐olds repeated back Korean words. Some words occurred once whereas others occurred five times. After the session, a surprise old/new recognition task was administered. Both groups' repetition accuracy improved for recurring but not nonrecurring words. Latencies got shorter for all words. The groups were reliably able to recognize recurring but not nonrecurring words. However, the adults performed substantially better in this memory task with an explicit component. No advantages for children were detected.